The Utilization of Artificial Intelligence in Agriculture to Optimize Irrigation and the Application of Pesticides and Herbicides - Dr. Shah Alam Khan; Umaish Raza; Basit Ahmad; Muhammad Waqas; Hassan Mumtaz; Muhammad Asim; Dr K. Junaid; Hassan Zubair (Dialogue Social Science Review (DSSR), 2025)
The industry faces various issues as it seeks to address pressures today such as scarcity of resources in the natural world, degradation of the physical environment and the rising demand for produce by the increasing population globally. In light of such considerations, Artificial Intelligence AI has come up as an innovative tool that has the potential to revolutionise the agricultural sector. This paper also compares how AI can be implemented to enhance various priority aspects of agriculture; including water supply and pest control. This paper explored the role of AI in agriculture and how AI can provide innovative solutions for optimising efficiency, cutting operations costs and minimising environmental impacts through the application of machine learning algorithms, computer vision, the IoT and sensor technology. These technologies facilitate accurate measurements in real-time, decision support systems and enhance efficient farming known as precision agriculture. The goal of this paper is to show how AI can catalyse a new generation of more sustainable, efficient, and economically sustainable agriculture which would help the industry tackle emerging challenges in the future.